Corporate social responsibility and firm performance of local and multinational firms in Penang Malaysia - Olagoke, Ilesanmi (2015)
This study examined the relationship between corporate social responsibility (CSR) and firm performance between the multinational and local companies in Penang, Malaysia. Corporate social responsibility (CSR) in this study is dimensionalised into the community development CSR, human resources CSR and environmental contribution CSR. The study used a convenience sampling technique to collect primary data from 113 multinational and local companies in Penang, through a self-administered survey questionnaire and which was analysed with statistical package for social sciences (SPSS) version 20 software. The findings show that community development CSR, human resources CSR and environmental contribution CSR have positive relationship with firm performance. In addition, the findings revealed that there is a significant difference between multinational companies and local companies in their practice of corporate social responsibility